Towards low carbon economy via carbon intensity reduction in Malaysia - Abdul Rahim, Khalid (International Institute for Science, Technology & Education, 2014)
Reducing carbon intensity has been pledged by many countries at many previous UN talks. The objectives of this paper are to analytically review the trends in carbon emissions in the energy sector, to assess the potential reversibility of the growth of carbon emissions and carbon intensity in the energy sector through the use of renewable resources and recommend a roadmap to achieve a low carbon economy target by 2020 with implications on the development of renewable energy resources in the country. Given the GDP growth rate of 5% per annum Malaysia will fail to meet its target of CO2 intensity reduction. However, Malaysia can still achieve its target CO2 intensity by 2020 by reducing the growth in the total CO2 emissions from the power generation sector from 5.79% per annum under the business-as-usual scenario to 0.785% per annum. Reductions in the rate of growth of carbon emissions from the power generation sector can be implemented through initiatives to increase the use of renewable energy resources. Emphasis has been given to the development of RE focusing on harnessing energy from resources such as solar, biomass, mini-hydro, wind and tidal energy.